Teachers’ Poor Professionalism Of Writing A Scientific Paper at Muhammadiyah Senior High School In Central Java - Bambang Sumardjoko (International Journal of Pedagogy and Teacher Education, 2018)
The paper aims at analyzing teachers’ poor professionalism of writing a scientific paper at Muhammadiyah Senior High School in Central Java. It studies on the phenomena of teachers’ weaknesses, comprehension, efforts and constraints on writing a scientific paper. The study belongs to qualitative research by applying a descriptive approach in examining the problem. The data are got with an in-depth interview, observation, and document analysis. The data sources are teachers, headmaster, a chief of High and Preliminary Education Assembly, and educational experts. Data validation is conducted by methods and sources triangulation. The data analysis applies the interactive model.The research result shows that most teachers have a limited comprehension of scientific paper concepts, skill on conducting classroom action research and writing a scientific paper. Also, they also have some constraints such as lack of writing motivation, school infrastructure, and internet connection access. In eliminating those problems, firstly Muhammadiyah senior high school (SMA/MA/SMK) teachers of Sukoharjo district have done some activities to develop their professional competence especially in the field of writing a scientific paper. In supporting their efforts, it needs a concrete step of stakeholder to simplify of all regarding with learning administrative activities, facilities adequacy motivation, the initiative of Assembly of Elementary and Middle Education, and others sponsorship, as well as the guidance of university.